Recharacterization of Rhinophis dorsimaculatus Deraniyagala, 1941 (Serpentes: Uropeltidae), including description of new material - Gower, David J.; Wickramasinghe, L. J. Mendis (Zootaxa, 2016)
The Sri Lankan uropeltid (shieldtail) snake Rhinophis dorsimaculatus Deraniyagala, 1941 was described originally from two specimens that were subsequently lost. The small amount of previously published data and lack of published colour photographs made this one of South Asia’s most poorly known snake species, and this resulted in at least one instance of taxonomic misidentification. An additional 10 specimens from a historical collection from the vicinity of the type locality recently came to light. This material is reviewed and documented and the species recharacterized. An additional locality for the species is reported. The newly reported material helps to corroborate the taxonomic validity and distinctiveness of Rhinophis dorsimaculatus. The species is readily distinguished from congeners by having 227 or more ventral scales; a large, dorsally carinate rostral shield; posterior margins of paired anals that are largely separated by the posteriormost ventral scale; and a distinctive colour pattern with bilaterally asymmetrical dark blotches within a broad, pale middorsal stripe and regularly punctate flanks.